The Use of Orature in the Depiction of the Conflict Between the Luo and the Lang’o in the Play Lwanda Magere by Okoiti Omtatah. - Tayebwa, Shyness (Kabale University, 2024)
The study examined the use of orature in the depiction of the conflict between the Luo and the Lang’o in the play Lwanda Magere by Okoiti Omtatah. The study was guided by objectives which were to analyze how Omtatah employs elements of orature such as songs, proverbs, riddles, myths, rituals, and storytelling techniques to depict the Luo-Lang’o conflict in the play Lwanda Magere, to examine how the depiction of conflict between the Luo and Lang'o in the play Lwanda Magere through orature contributes to the understanding of inter-community relations, power dynamics, and socio-political tensions and to explore the causes of conflict within the Luo and Lang'o communities as portrayed through the orature in the play Lwanda Magere. The study was based on critical and in-depth internalization of the play, careful reading of relevant books, authentic use of journals and articles and accurately relating them to the topic of study. The study adopted a descriptive approach that helped in analyzing information in a systematic way in order to come up with useful recommendations and conclusions on the use of orature. The play Lwanda Magere acts as the main research instrument and the use of documentary guides has been successfully incorporated. The data was analyzed through descriptive and textual analysis. It thus affirmed that the use of orature in depicting conflict is manifested through storytelling, proverbs, and sayings. This research allowed us to understand the degree to which orature helps in cultural preservation and imparts moral lessons to society. It proved that Omtatah impacts society through orature because the play Lwanda Magere is profound, enriching the narrative with cultural authenticity, mythological depth, moral complexity, and audience engagement. Through the use of oral tradition and storytelling, the play brings to life the legend of Lwanda Magere in a way that resonates with audiences and honors the oral heritage of the Luo people. All this was discussed in the subsequent chapters of this research report.